RP Lidar Sensor for Multi-Robot Localization using Leader Follower Algorithm - Issa, Bayadir A.; Rashid, Abdulmuttalib T. (Iraqi Journal for Electrical and Electronic Engineering, 2019)
In this paper, a new technique for multi-robot localization in an unknown environment, called the leader-follower localization algorithm is presented. The framework utilized here is one robot that goes about as a leader and different robots are considered as followers distributed randomly in the environment. Every robot equipped with RP lidar sensors to scan the environment and gather information about every robot. This information utilized by the leader to distinguish and confine every robot in the environment. The issue of not noticeable robots is solved by contrasting their distances with the leader. Moreover, the equivalent distance robot issue is unraveled by utilizing the permutation algorithm. Several simulation scenarios with different positions and orientations are implemented on (3- 7) robots to show the performance of the introduced technique.